Industrial relations and working conditions developments in Europe 2012 - European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2013)
This report describes the developments in industrial relations and working conditions in 2012 in the 27 EU Member States, in Croatia (not yet a Member State in 2012, but included in the comparative analysis) and Norway. It also considers policies, initiatives and legislative developments in EU-level industrial relations and working conditions taking into account the economic situation and responses to it. In the past, Eurofound has analysed trends in working conditions and industrial relations in two separate reports. But due to the important interdependences between the two areas, developments in working conditions and industrial relations are now combined into a single annual report.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Hours of labor -- European Union countries; Industrial relations -- European Union countries; Working conditions -- European Union countries; European Union countries -- Social conditions; Electronic books